Harga Properti Residensial & Pembiayaan Pemilikan Rumah Perbankan Syariah dan Konvensional - Christine Ullyana; Heny K Daryanto; Imam T Saptono (Department of Islamic Economics, IPB University, 2016)
. This study investigates the dynamic relationship between macroeconomic variables and housing financing provided by convensional and islamic banking in Indonesia. Utilizing quarterly data from 2007 to 2016, this study employs Vector Error Correction Model (VECM), Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD). It finds that macroeconomics variables and housing price have distinct long relationship with housing financing provided by both. Our study reveal that policy intervention to stimulate or dampen housing financing provided by islamic and conventional bank can focus on GDP, house prices and monetary policy however it should be implemented to right segment. In addition, this study documents evidence that Islamic housing financing in Indonesia really dependent on interest rate. Therefore the findings suggest that Islamic Banking could apply alternative rate, possibly IHPR to manage to live up to their ideals in achieving the objectives of Shari’ah